Reproductive response of postpartum spring-lambing ewes: effects of weaning on follicular growth and postpartum interval on response to ram placement with ewes (ram effect) - Ungerfeld, Rodolfo; Kako Rodriguez, Mariana Garcia [UNESP]; Perez-Clariget, Raquel (Elsevier B.V., 2020)
The aim of the first experiment was to determine if follicular growth rate in ewes increases spontaneously or after gonadotropin administration after lamb weaning during the period of seasonal anestrus. To conduct this experiment, there were postpartum lactating ewes from which lambs were or were not weaned when 68 to 72 days old (Day 0). The ovaries were assessed using ultrasonography from Day 0 to 9, followed by the administration of 200 IU of eCG on Day 7 to all ewes to determine capacity of follicles to respond to gonadotropin stimulation. There were no differences in duration of follicular wave dynamics, or maximum dominant follicle diameter during the first follicular wave after lamb weaning or after administration of eCG. Because weaning did not have positive effects on follicular development, the aim of the second study was to compare responses to placement of rams with lactating ewes (47 or 68 days postpartum; PP47 and PP68, respectively) and seasonal anestrous ewes that lambed during the previous year (Control). There were no differences in the proportion of ewes of the three groups that developed a corpus luteum after placement with rams, but more ewes of the Control than PP47 and PP68 groups expressed behavioral estrus and lambed as a result of placement of ewes with rams (P < 0.0001). In extensive grazing management systems, weaning of lambs did not modify spontaneous or induced follicular growth in Corriedale ewes that lambed in the spring. The placement of rams with ewes resulted in induction of ovulations, estrus and pregnancies even when ewes have lambs suckling.
Keywords: Follicle; Lactational anestrus; Seasonality; Reproductive performance